2012
DOI: 10.1097/mph.0b013e3182446a60
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Interleukin-6 and Interleukin-8 for Early Prediction of Bacteremia and Sepsis in Children With Febrile Neutropenia and Cancer

Abstract: These interleukins could be used as a screening tool for the rejection of sepsis or bacteremia on the first day of fever in neutropenic children with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…[12,13] Though CRP is widely used as a marker for bacterial infection, it has several disadvantages including delayed increase and low specificity. [14] Akin to our study, Urbonas et al, [15] demonstrated high NPV on day 1 for IL-6 and IL-8 (89% and 82%, respectively) for exclusion of bacteraemia/sepsis in 61 episodes of FN. The authors concluded that IL-6/8 and IL-8 could not reliably predict bacterial infection because of low sensitivity and PPV; however, they could be useful for excluding patients with bacteraemia or clinical sepsis.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…[12,13] Though CRP is widely used as a marker for bacterial infection, it has several disadvantages including delayed increase and low specificity. [14] Akin to our study, Urbonas et al, [15] demonstrated high NPV on day 1 for IL-6 and IL-8 (89% and 82%, respectively) for exclusion of bacteraemia/sepsis in 61 episodes of FN. The authors concluded that IL-6/8 and IL-8 could not reliably predict bacterial infection because of low sensitivity and PPV; however, they could be useful for excluding patients with bacteraemia or clinical sepsis.…”
Section: Discussionmentioning
confidence: 46%
“…The authors concluded that IL-6/8 and IL-8 could not reliably predict bacterial infection because of low sensitivity and PPV; however, they could be useful for excluding patients with bacteraemia or clinical sepsis. [15] Their best cut-off levels were higher than in our study. Lehrnbecher et al, [16] evaluated 311 febrile episodes in three paediatric cancer centres.…”
Section: Discussionmentioning
confidence: 60%
“…A notable problem with implementation of TNF- α as a routine diagnostic biomarker is its undetectable serum level in a significant percentage of patients with a proven Gram-positive bacterial infection of moderate disease severity [12]. Similar to TNF- α , low or undetectable IL-6 serum levels are reported for some patients with severe bacterial infections, which limits its usefulness for ruling out sepsis and bacteremia [13]. IL-6 levels are often below detectable limits, but IL-6 is considered a stress-related proinflammatory cytokine that usually correlates with CRP and is often used as a biomarker of acute and chronic inflammation [1416].…”
Section: Discussionmentioning
confidence: 99%
“…As blood cultures can identify infectious etiologies of FN with a likelihood of just 20 % [1], a fever-driven approach using broad-spectrum antibiotics is still common in daily practice, probably resulting in overtreatment, increased costs, and induction of drug-resistance in bacteria. Previous reports showed that procalcitonin (PCT), C-reactive protein (CRP) and some cytokines such as interleukin (IL)-6 and IL-8 may be helpful in diagnosing or ruling out bacterial infections in the management of FN [2][3][4][5][6][7][8][9][10][11]. To date, no strategy based on these tests has been established as a standard of care for FN.…”
Section: Introductionmentioning
confidence: 99%